Doping limitation due to self-compensation by native defects in In-doped rocksalt CdxZn1−xO. (19th November 2021) - Ho, Chun Yuen; Li, Chia Hsiang; Liu, Chao Ping; Huang, Zhi-Quan; Chuang, Feng-Chuan; Yu, Kin Man
Abstract: Cadmium oxide (CdO)–ZnO alloys (Cd x Zn1− x O) exhibit a transformation from the wurtzite to the rocksalt (RS) phase at a CdO composition of ∼70% with a drastic change in the band gap and electrical properties. RS–Cd x Zn1− x O alloys ( x > 0.7) are particularly interesting for transparent conductor applications due to their wide band gap and high electron mobility. In this work, we synthesized RS–Cd x Zn1− x O alloys doped with different concentrations of In dopants and evaluated their electrical and optical properties. Experimental results are analyzed in terms of the amphoteric native defect model and compared directly to defect formation energies obtained by hybrid density functional theory (DFT) calculations. A saturation in electron concentration of ∼7 × 10 20 cm −3 accompanied by a rapid drop in electron mobility is observed for the RS–Cd x Zn1− x O films with 0.7 ⩽ x < 1 when the In dopant concentration [In] is larger than 3%. Hybrid DFT calculations confirm that the formation energy of metal vacancy acceptor defects is significantly lower in RS–Cd x Zn1− x O than in CdO, and hence limits the free carrier concentration. Mobility calculations reveal that due to the strong compensation by native defects, RS–Cd x Zn1− x O alloys exhibit a compensation ratio of >0.7 for films with x < 0.8. As a consequence of the compensation by native defects, in heavily doped RS–Cd x Zn1− x O carrier-induced band filling effect is limited. Furthermore, the much lower mobility of the RS–Cd x Zn1− x O alloys also results in a higher resistivity and reduced transmittance in the near infra-red region (λ > 1100 nm), making the material not suitable as transparent conductors for full spectrum photovoltaics.